1967
DOI: 10.1038/bjc.1967.84
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of steroid hormone concentrations in human tissues including breast cancer.

Abstract: STUDIES with human tissue slices in vitro (Braunsberg and James, 1967a) showed that many tissues are capable of binding steroid hormones. Muscle bound relatively little, while adipose tissue showed the largest uptakes of testosterone, oestradiol and progesterone from saline solution. One of ten malignant tumour samples studied took up a relatively large amount of testosterone, but this did not exceed the uptake by adipose tissue. During incubation in serum albumin solution or plasma, little or no steroid was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

1967
1967
1979
1979

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Analysis of tissue radioactivity after constant infusions of the labelled material in vivo provides a more convenient basis of comparison with in vitro equilibration experiments (Braunsberg and James, 1967). Such a study with labelled testosterone (Braunsberg, Irvine and James, 1967), like the in vitro studies reported here, failed to reveal any marked specific uptake of radioactivity by breast tumour tissue. The in vitro uptake of adipose tissue in relation to that of muscle appears to be rather higher than that in vivo.…”
Section: Tissue Steroid Uptake Ratiosmentioning
confidence: 53%
See 4 more Smart Citations
“…Analysis of tissue radioactivity after constant infusions of the labelled material in vivo provides a more convenient basis of comparison with in vitro equilibration experiments (Braunsberg and James, 1967). Such a study with labelled testosterone (Braunsberg, Irvine and James, 1967), like the in vitro studies reported here, failed to reveal any marked specific uptake of radioactivity by breast tumour tissue. The in vitro uptake of adipose tissue in relation to that of muscle appears to be rather higher than that in vivo.…”
Section: Tissue Steroid Uptake Ratiosmentioning
confidence: 53%
“…A sample of adipose tissue incubated with testosterone in the patient's plasma gave a ratio of 2-2. Quantitative comparisons between in vitro equilibration and single injection of the labelled substance in vivo (Stone andBaggett, 1965, 1966) are complex and would require careful mathematical analysis (Braunsberg and James, 1967). Analysis of tissue radioactivity after constant infusions of the labelled material in vivo provides a more convenient basis of comparison with in vitro equilibration experiments (Braunsberg and James, 1967).…”
Section: Tissue Steroid Uptake Ratiosmentioning
confidence: 99%
See 3 more Smart Citations